2009
DOI: 10.5483/bmbrep.2009.42.8.523
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of phosphomannose isomerase from sphingomonas chungbukensis DJ77

Abstract: Phosphomannose isomerase (PMI) catalyzes the interconversion of fructose-6-phosphate and mannose-6-phosphate in the extracellular polysaccharide (EPS) synthesis pathway. The gene encoding PMI in Sphingomonas chungbukensis DJ77 was cloned and expressed in E. coli. The pmi gene is 1,410 nucleotides long and the deduced amino acid sequence shares high homology with other bifunctional proteins that possess both PMI and GDP-mannose pyrophosphorylase (GMP) activities. The sequence analysis of PMI revealed two domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…1 ). The conserved VEKP sequence included in the GMP active site is a mannose-1-phosphate binding site of GMP 27 . To examine the relationship between the three DoGMP proteins and other GMP members in plants, a phylogenetic analysis was performed among GMP protein sequences using MEGA 4 28 .…”
Section: Resultsmentioning
confidence: 99%
“…1 ). The conserved VEKP sequence included in the GMP active site is a mannose-1-phosphate binding site of GMP 27 . To examine the relationship between the three DoGMP proteins and other GMP members in plants, a phylogenetic analysis was performed among GMP protein sequences using MEGA 4 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Biosynthesis of the characteristic compounds for exopolysaccharide production by L. casei LC2W EPSs, which have been isolated from the skim milk produced by L. casei LC2W, are composed of four monosaccharides, i.e., D-glucose, D-galactose, D-rhamnose, and D-mannose (Ai et al, 2008). These monosaccharides seemed to be released individually by UDP-glucose, UDP-galactose, dTDP-rhamnose, and GDP-mannose (Jensen and Reeves, 2001;Johnson et al, 2005;Tran et al, 2009). The genome annotation indicated that L. casei LC2W could synthesize UDP-glucose, UDP-galactose, and dTDPrhamnose via successive catalytic reactions using the enzymes Pgm, RffH, RfbB, RfbC, RfbD, GtaB, GalE, and GalT (Fig.…”
Section: Production Of Lactate and Flavor Compounds By L Casei Lc2wmentioning
confidence: 98%
“…14,15,34 This bacterium has the potential to produce exopolysaccharides (EPS), which can be used as a gelling agent for various pharmaceutical and industrial processes, because some genes encoding functional enzymes (i.e., phosphomannose isomerase and phosphoglucose isomerase) involved in EPS biosynthesis pathways have been isolated through its genomic analysis. 35,36 EPS levan, which is synthesized by levansucrase, is a fructantype homopolysaccharide with β-(2,6) glycosidic linkages. 37 It is useful in a wide range of applications including food, feed, cosmetics, and medicine due to its uncommon properties, for example, low intrinsic viscosity from other polysaccharides.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Sphingobium chungbukense DJ77, isolated from contaminated sediment of an industrial complex near Daejon, Republic of Korea, is a Gram-negative bacteria strain. We previously reported that it is useful for the synthesis of sphingolipids and for the degradation of poly- and monocyclic aromatic hydrocarbons such as phenanthrene, anthracene, toluene, m -xylene, phenol, salicylate, benzoate, and p -cresol. ,, This bacterium has the potential to produce exopolysaccharides (EPS), which can be used as a gelling agent for various pharmaceutical and industrial processes, because some genes encoding functional enzymes (i.e., phosphomannose isomerase and phosphoglucose isomerase) involved in EPS biosynthesis pathways have been isolated through its genomic analysis. , …”
Section: Discussionmentioning
confidence: 99%